(untitled) - Kumar, Anil (New York, 1998)
After an introduction to polymer as materials, the book elucidates the mechanisms of polymerization and their effect on the engineering design of reactors; its considers polymer characterization, polymer thermodynamics, and the behavior of polymers as melts, solutions, and solids both above and below the glass transition temperature. It also examines crystallization, diffusion of and through polymers, and polymer processing
Keywords: Polymerization,Polymers